A Note on Statistical Limit and Cluster Points of The Arithmetical Functions ap(n), γ(n), and τ(n) in The Sense of Density - Abdu Awel Adem; Mehmet Kucukaslan (IndoMS, 2020)
In this paper, by using natural density of subsets of N, the statistical limit and cluster points of the arithmetical functions (ap (n)), γ (n),τ(n), Δ γ (n) and Δ τ (n) are studied. In addition to this, we also investigate statistical limit and cluster points of (Δ r γ (n) and (Δ r τ (n)) for each r ın N.